If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(2x + -6) = 3(6x + 9) Reorder the terms: 9(-6 + 2x) = 3(6x + 9) (-6 * 9 + 2x * 9) = 3(6x + 9) (-54 + 18x) = 3(6x + 9) Reorder the terms: -54 + 18x = 3(9 + 6x) -54 + 18x = (9 * 3 + 6x * 3) -54 + 18x = (27 + 18x) Add '-18x' to each side of the equation. -54 + 18x + -18x = 27 + 18x + -18x Combine like terms: 18x + -18x = 0 -54 + 0 = 27 + 18x + -18x -54 = 27 + 18x + -18x Combine like terms: 18x + -18x = 0 -54 = 27 + 0 -54 = 27 Solving -54 = 27 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 9(y-2)+5(6y-18)-13y=-4 | | 6-5x+9+3x+3x-2=8+3(4) | | 5y-10=4y-1 | | 8+18z-3=9z+35-6z | | 0=(3x+2)(4x-1) | | [3x-4(x+1)]=2 | | 5p+9p=70 | | -4m-7+13m-12+2m-5= | | p^2+11+10=0 | | x/3=-26 | | X/-14 | | 11.9x=35.7 | | [3z-2]=1 | | 4/9+2+2/8 | | [5-7r]=3 | | -9v-81=-108v+18 | | 3[2-x]=-6 | | 2k^2+11k+30=0 | | 7x-10=-59 | | y=3.5x-0.1 | | -9x-7=10x+2 | | 2x+12=16+2x | | 8+2(3x-5)-7x+6y=16 | | 9n^2+75n+150=0 | | 4x-101=-3x+81 | | -80+5x=-4x+154 | | 14-9t+2=-t+30 | | [x-7]=12 | | x+7/4X=55 | | -162+3x=-6x+72 | | 7x^2-30x=8 | | 5-[p+6]=-8 |